Seeing power art and activism in the 21st century - Thompson, Nato 1972- (Melville House, 2015)
In our chaotic world of co-opted imagery, does art still have power? A fog of images and information permeates the world nowadays: from advertising, television, radio, and film to the glut produced by the new economy and the rise of social media . . . where even our friends suddenly seem to be selling us the ultimate product: themselves. Here, Nato Thompson-one of the country's most celebrated young curators and critics-investigates what this deluge means for those dedicated to socially engaged art and activism. How can anyone find a voice and make change in a world flooded with such pseudo-art? How are we supposed to discern what's true in the product emanating from the ceaseless machine of consumer capitalism, a machine that appropriates from art history, and now from the methods of grassroots political organizing and even social networking? Thompson's invigorating answers to those questions highlights the work of some of the most innovative and interesting artists and activists working today, as well as institutions that empower their communities to see power and reimagine it. From cooperative housing to anarchist infoshops to alternative art venues, Seeing Power reveals ways that art today can and does inspire innovation and dramatic transformation . . . perhaps as never before
Includes bibliographical references
Keywords: Geschichte 2000-2015; Politik; Arts -- Political aspects; Art and social action; Aktivismus; Kunstkritik; Kunst; Soziologie; Aufsatzsammlung